1978
DOI: 10.1007/bf00426903
|View full text |Cite
|
Sign up to set email alerts
|

The effect of housing and gender on morphine self-administration in rats

Abstract: To determine the effect of housing conditions on morphine self-administration, rats isolated in standard laboratory cages and rats living socially in a large open box (8.8 m2) were given morphine in solution (0.5 mg/ml) as their only source of fluid for 57 days. They were then exposed to a series of 3-day cycles previously shown by Nichols et al. (1956) to increase self-administration of morphine in caged rats. On morphine/water choice days late in the period of forced consumption, between the Nichols cycles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
125
3
16

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(157 citation statements)
references
References 17 publications
13
125
3
16
Order By: Relevance
“…Although a growing body of evidence suggests that females are more prone to drug self-administration than males (Alexander et al, 1978;Lynch and Carroll, 1999;Carroll et al, 2001;Cicero et al, 2003;Hu et al, 2004;Roth et al, 2004), we found no differences in the acquisition of male and female mice. However, it is noteworthy that choice accuracy for the morphine-reinforced arm of the maze reached a maximum in female WT mice, with over 95% of drug-reinforced responses for 4 out of 6 self-administration sessions.…”
Section: Discussioncontrasting
confidence: 93%
“…Although a growing body of evidence suggests that females are more prone to drug self-administration than males (Alexander et al, 1978;Lynch and Carroll, 1999;Carroll et al, 2001;Cicero et al, 2003;Hu et al, 2004;Roth et al, 2004), we found no differences in the acquisition of male and female mice. However, it is noteworthy that choice accuracy for the morphine-reinforced arm of the maze reached a maximum in female WT mice, with over 95% of drug-reinforced responses for 4 out of 6 self-administration sessions.…”
Section: Discussioncontrasting
confidence: 93%
“…Alexander, Coambs, & Hadaway, 1978), amphetamine (Bardo, Klebaur, Valone, & Deaton, 2001) or cocaine (Gipson, Beckmann, ElMaraghi, Marusich, & Bardo, 2011) Humans in three different conditions consumed more snacks when they selfreported increased boredom (Moynihan et al, 2015) Mink without environmental enrichment consumed more food rewards than mink with environmental enrichment (Meagher & Mason, 2012) Polydipsia As with polyphagia, animals in the monotonous condition should drink and urinate more frequently, even excessively NF Three laboratory rabbits drank and urinated excessively; no health abnormalities were found, and provision of toys and manipulanda successfully reduced the behaviour (Potter & Borkowski, 1998).…”
Section: Psychoactive Drug Consumptionmentioning
confidence: 99%
“…Es a partir de allí que Zinberg expone su famoso triángulo, en donde los efectos del consumo de cualquier droga no dependen solamente de las propiedades farmacológicas de la misma, sino también de su interacción con lo que el autor denominó Set & Setting (sujeto y contexto respectivamente). En la misma década, Bruce Alexander y su equipo llegan a conclusiones similares, pero a través de la experimentación con modelos animales (Alexander, Coambs, & Hadaway, 1978). Bajo la hipótesis de que el consumo excesivo de una sustancia es consecuencia de las condiciones experimentales displacenteras creadas en el laboratorio dentro de la "jaula de Skinner", Alexander y colaboradores deciden diseñar un "Parque de Ratas".…”
Section: La Encrucijada De La Dependencia Psicológicaunclassified